Расчетные и экспериментальные исследования проточных частей ПЛ20 для модернизации гидротурбин Кременчугской гидроэлектростанции - Линник, А.В.; Рябова, С.А.; Варенко, В.Д.; Рябов, А.В.; Хорев, О.Н. (Проблемы машиностроения, 2016)
Одним из приоритетных направлений развития гидроэнергетики Украины является модернизация морально и физически изношенного гидроэнергетического оборудования гидроэлектростанций, отработавшего 40-50 лет. Главными задачами реконструкции ГЭС' является продление срока ее эксплуатации, увеличение мощности, повышение эффективности, надежности и безопасности оборудования и конструкций, соответствие требованиям защиты окружающей среды, улучшение качества производимой энергии, а также создание современных условий работы. Наведено результати комплексних розрахунково-теоретичних і експериментальних досліджень проточних частин модельних гідротурбін ПЛ20 для модернізації Кременчуцької гідроелектростанції. Експериментальні дослідження проведені на універсальному енергокавітаційному стенді ПАТ «Турбоатом». Наведено експериментальні залежності відносного коефіцієнта корисної дії моделі від приведеної витрати, а також порівняння енергетичних і кавітаційних показників випробуваних проточних частин з удосконаленими лопатями робочих коліс і лопатками направляючого апарата для оптимальних режимів роботи гідротурбіни. One of the priority directions of development of hydropower engineering in Ukraine is the rehabilitation of obsolescent and worn-out hydropower equipment for hydro power plant, served for 40-50 years. The major concerns of hydro power plant reconstruction are time extension of its operation, capacity increase, effectiveness increase, reliability and safety of equipment and structures, compliance with the requirements of environmental protection, improvement in quality of produced power, and creation of modern working conditions. The capital equipment of Kremenchug hydro power plant reached the end of its standard service life and is not equal in full measure to the modern requirements of the power system. Rehabilitation of the hydraulic equipment provided for the improvement of the main working bodies of the flow parts: the runner and the guide vanes within limits of existing sizes of the inlet and outlet bodies. Two stages of rehabilitation of the flow parts of hydraulic turbines of Kremenchug hydro power plant have been carried out: reconstruction of two units (station № 2 and № 3) for the first stage and three units (station № 7, № 8 and № 9) for the second one. The principal indicators of contractual conditions fulfillment for the rehabilitation were to provide values of nominal and maximum capacity, efficiency, cavitation stock, the valid range of work loads, etc. The complex of theoretical and experimental investigations on the development of blade systems for rehabilitation of hydraulic turbines PL20 Kremenchug hydro power plant has been carried out. The experimental dependences of the relative efficiency of the model from the reduced discharge and comparison the energy and cavitation parameters of tested flow parts at the optimal operating conditions are given. The advantage of improved flow parts on energy and cavitation characteristics is shown. PJSC "Turboatom" has confirmed the contractual conditions that ensure the values of nominal and maximum capacity of turbine, achievement of a weight average efficiency, cavitation performances and etc. according to the functional guarantees. Advanced runners and guide vanes have been manufactured and mounted on the hydraulic units № 2 and № 3, these units have been put into operation. The hydraulic unit № 7 with advanced runner and guide vanes has been put into operation after rehabilitation. The hydraulic units № 8 and № 9 are in the reconstruction stage. The third stage of reconstruction of Kremenchug hydro power plant is planned – two units (station № 1 and № 4).